Analisis Pengaruh Brand Equity, Promosi, dan Kualitas Produk Terhadap Minat Beli Konsumen Produk Minuman Viral Mixue Di Jombang - Arrosyid, Muhammad Awab; Arifin , Muhyiddin Zainul; Bisari, Nia Aprilia (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2024)
This research was conducted to identify whether there is any influence between brand equity, promotion, product quality on buying interest of the Mixue Viral drink product in Jombang. This study uses an associative method with a quantitative approach. The population in this study were mixue consumers in the city of Jombang, especially the Ringin Contong Mixue Outlet, Jl. A. Yani No. 2, Jombang, Kec. Jombang, Jombang Regency, East Java. To obtain data that is in accordance with this study, researchers used a questionnaire as a medium in collecting data and used the Non-Probability Sampling technique using the Accidental Sampling method in determining the respondents. Total respondents in this study were 100 respondents. which was then analyzed using multiple regression analysis using SPSS version 21. The results showed that partially the brand equity variable had a positive and significant effect on consumer buying interest, the promotion variable had a positive and significant effect on consumer buying interest, while the product quality variable also had a positive and significant effect significant effect on consumer buying interest. Simultaneously, the variables brand equity, promotion, product quality have a positive and significant effect on consumer buying interest for the viral Mixue drink product in Jombang.